2014
DOI: 10.12659/msm.891017
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of IL-13 Polymorphisms and Pediatric Asthma Risk

Abstract: BackgroundIL13–1112C/T and +2044A/G polymorphisms have been reported to be correlated with pediatric asthma susceptibility, but study results were still debatable. Thus, a meta-analysis was conducted.Material/MethodsPubMed and EMBASE databases were searched. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to calculate the strength of association in the random-effects model or fixed-effects model.ResultsFourteen case-control studies with 4710 asthma cases and 6086 controls were included in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…These asthma GWAS have used a range of asthma definitions, including physician diagnosis in GABRIEL, electronic medical record information in eMERGE, and physicians’ diagnosis and/or standardized questionnaires in the TAGC [ 4 , 24 , 47 ]. A number of prior GWAS have identified distinct genetic susceptibility for pediatric onset asthma, particularly implicating ORLDM3 / GSDMB , IL1RL1 , and IL13 , which were all found to have association with childhood asthma in the current analysis [ 4 , 5 , 6 , 7 , 24 , 59 ]. C11orf30-LRRC3 , which also has association in this GWAS, has been associated with in pediatric asthma previously, though in prior GWAS the primary link with asthma has been in the setting of allergic disease [ 33 , 60 ].…”
Section: Discussionmentioning
confidence: 94%
“…These asthma GWAS have used a range of asthma definitions, including physician diagnosis in GABRIEL, electronic medical record information in eMERGE, and physicians’ diagnosis and/or standardized questionnaires in the TAGC [ 4 , 24 , 47 ]. A number of prior GWAS have identified distinct genetic susceptibility for pediatric onset asthma, particularly implicating ORLDM3 / GSDMB , IL1RL1 , and IL13 , which were all found to have association with childhood asthma in the current analysis [ 4 , 5 , 6 , 7 , 24 , 59 ]. C11orf30-LRRC3 , which also has association in this GWAS, has been associated with in pediatric asthma previously, though in prior GWAS the primary link with asthma has been in the setting of allergic disease [ 33 , 60 ].…”
Section: Discussionmentioning
confidence: 94%
“…For example, IREB2 gene rs2568494 polymorphism has been shown to be associated with susceptibility to chronic obstructive pulmonary disease [ 5 ]. IL13 gene polymorphisms contribute to the development of pediatric asthma [ 6 ]. The human leukocyte antigen (HLA) super-locus is a genomic region in chromosome position 6p21 that encodes the 6 classical transplantation HLA genes and at least 132 protein-coding genes that have important roles in the regulation of the immune system, as well as some other fundamental molecular and cellular processes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to highlight the strengths of our meta-analysis and acknowledge its weaknesses. The central advantage of this meta-analysis is the rigorous statistical review of data from the literature that cannot be achieved by any single study [ 38 40 ]. An unambiguous and strong association between DEFB1 SNPs and digestive diseases cannot be drawn from the results of a single study, but our approach confirmed this relationship by analyzing the results from multiple studies.…”
Section: Discussionmentioning
confidence: 99%